Research Trends of Opposition Political Parties in the World - Firdaus, Muhammad; Agustiyara; Raga Sitandang, Galang (Internasional Journal of Politics and Public Policy, 2024)
This study aims to study the trend of opposition political party research in the world to see the interest of authors in various countries regarding the theme of opposition political parties in the world and their language coverage. The research method applied in this study is a systematic literature review using 324 scientific articles sourced from the Scopus Database. Article review using the Vosviewer application. The results of the study show that in 2023 to 2024 there was a decrease in interest in the theme of opposition political parties as seen from the decrease in the number of articles uploaded to the Scopus database. Then Gizem Melek became the dominant author in researching related topics, with a total of 4 publications from 324 articles uploaded throughout 2023-2024 in the Scopus database. England is the dominant country in the list of articles on the theme of opposition political parties, with 63 articles uploaded from that country. The scope of discussion with the scope of social sciences is the main dominance of the analysis results, with a presentation of 64.7%. The results of this study contribute to the development of a research roadmap on opposition political parties. The limitation of this study is that the articles used are only sourced from the Scopus database, so that the research findings cannot comprehensively describe the problems faced by opposition political parties around the world. Therefore, further research needs to use scientific articles from other reputable international databases, such as Web of Science and Dimensions Scholars.